Some experimental results on fixed time artificial insemination (Mongolian Journal of Agricultural Sciences, 2019)
The fixed time of artificial Insemination was carried out in Holstein breed cows at the Max-Agro dairy farm. Four protocols with different combinations of gonadotropin realizing, prostaglandin and CIDR were used for the estrus synchronization of cows.  As result of the experimental work, the rate of estrus synchronization was at 86±4.6 % in the study. Conception rate was in average 48.8±15.5% and   totally 21 calves were born. The experimental protocols are shown that the CIDR+PG+GnRH combination was better than others schemes. That is why we would like to recommend that the estrus synchronization method with the CIDR+PG+GnRH is to be introduced into livestock reproduction practices.Цагийн зохицуулалттай зохиомол хээлтүүлэгийн үр дүнгээс Бид “Макс-Агро” ХХК –ийн эрчимжсэн аж ахуйн Голштейн үүлдрийн үнээнд “Цагийн зохицуулалттай зохиомол хээлтүүлэг”хийв.Үүний тулд гипоталамусын гонадотропин релизинг даавар /GnRH/, простагландин даавар /PGF2a/, үтрээний суулгац (сидр)-ыг 4 өөр хувилбараар хослуулан хэрэглэхэд туршилтад хамрагдсан нийт үнээний 86±4.6 хувь нь ороо жигдрэв.Цагийн зохицуулалттай зохиомол хээлтүүлэг хийхэд дунджаар 48.8±15.5% хээл хөгжиж, 21 тугал хүлээж авлаа. Туршилт хийсэн хувилбаруудаас CIDR+PG+GnRH-ийг хослуулан хэрэглэн ороо жигдрүүлж үнээнд цагийн зохицуулалттай зохиомол хээлтүүлгийн аргыг үйлдвэрлэлд нэвтрүүлэх зүйтэй гэж үзэж байна. Түлхүүр үг: Гонадотропин релизинг даавар, простагландин, ороо, цагийн зохицуулалттай зохиомол хээлтүүлэг